Pengaruh Penerapan Metode Mengajar Latihan Terhadap Kemampuan Gerak Dasar Menendang Bola Menggunakan Kaki Bagian Luar Pada Siswa SMP Negeri 1 Touluaan - Putra Kading (Jurnal Praba : Jurnal Rumpun Kesehatan Umum, 2025)
This study aims to analyze the effect of the practice teaching method on the basic motor skill of kicking a ball using the outside foot among students of SMP Negeri 1 Touluaan. The research was a quasi-experimental design with a quantitative approach. A total of 20 students were divided into two groups: an experimental group receiving the practice teaching method, and a control group receiving no intervention. The instrument used was a test of kicking skills. Data were analyzed using a t-test after the prerequisites of normality and homogeneity were met. The result showed tcount = 3.81 > ttable = 2.101 at a significance level of 0.05, indicating a significant effect of the practice teaching method on the improvement of basic kicking skills using the outside foot.